Itinerancy effects on spin correlations in one-dimensional Mott insulators - Bhaseen, M; Essler, F; Grage, A (2005)
We consider spin correlations in the one-dimensional (1D) half-filled repulsive Hubbard model. For very large values of the on-site repulsion U the spin correlations are dominated by virtual hopping processes of electrons and are described in terms of a spin-1/2 Heisenberg chain. As U is decreased real hopping processes of electrons become important and eventually dominate the spin response. We discuss the evolution of the dynamical structure factor as a function of U. We comment on the relevance of our results for inelastic neutron-scattering experiments on quasi-1D materials. ©2005 The American Physical Society.